Exact Linearization Techniques to Analyze the Population Dynamics of the Dengue Fever Vector - de Oliveira Florentino, Helenice [UNESP]; Cantane, Daniela Renata [UNESP]; dos Reis, Célia Aparecida [UNESP]; Cólon, Diego; Fleury Rosa, Suélia Rodrigues (Springer Nature, 2020)
This work presents an analysis of a mathematical model describing the population dynamics of Aedes aegypti and the design of a vector control via exact linearization techniques and optimal control. The control strategy optimizes the use of resources for vector control. Theoretical and computational results are presented.
Keywords: Control; Dengue fever; Mathematical model; Transmission